The relationship between macroeconomic variables and capital structure decisions: empirical evidence from Botswana and Mauritius - Chimbwete, Ngodya (My University, 2019)
The relationship between the impact of macroeconomic variables and capital structure decisions has been extensively researched through the years and across many countries. Despite the extensive research done, these studies have not been conclusive. This research paper studies this relationship of the impact of selected macroeconomic variables on the capital structure of companies in Botswana and Mauritius. These countries were chosen due to their differences in economic structure; Botswana has been seen to be a resource-based economy whilst Mauritius has been seen to been diversified economy. Furthermore, Stock Market Capitalization (MC) and Credit Growth in each country, were used as proxies for capital structure decisions. Results were both in support of and contrary to the theory and therefore arrived at the conclusion that because Botswana and Mauritius are subjected different economic dynamics (resource-based and diversified economies) it can be inferred that firms in the various countries will need to adjust their capital structures depending on how these variables interact within their respective economies.
Thesis submitted in fulfilment of the requirements for the degree of Masters of Management in Finance and Investments in the Faculty of Commerce, Law and Management Wits Business School at the University of the Witwatersrand, 2017
Keywords: Macroeconomics; Capital--South Africa